Analisis Kinerja Keuangan Industri Gas Yang Terdaftar di BEJ (Studi Kasus PT. Aneka Gas Industri Tbk) - Dian Indah Sari; Slamet Maryoso (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2019)
Abstract- TTo find out the financial performance of PT. Aneka Gas Industri Tbk uses liquidity ratios, solvency ratios and profitability ratios for the period of 2016-2018 the purpose of this study. The research design used in this study is descriptive quantitative, namely data obtained from the sample population of the study and analyzed according to the statistical method used and then interpreted. From the discussion above it can be concluded that PT. Aneka Gas Industri Tbk The company requires ratio analysis such as liquidity ratios, solvency ratios and profitability ratios to provide an overview of the company's ability to pay debts, the ability to pay debts guaranteed by assets owned and the ability to obtain profits. Based on the calculation of the liquidity ratio, it can be said that the cash held by PT. Aneka Gas Industri Tbk has not been able to pay short-term debt. From the results of calculations using solvability ratios it can be said that companies are able to pay debts guaranteed by assets owned. The results of calculations with profitability ratios can be said that the company has not been able to obtain profits. Based on the calculation results, it can be concluded that the financial performance of PT. Aneka Gas Industri Tbk does not mean that the company has not been able to manage finances well. This can be seen from the liquidity ratio that has decreased, the solvency ratio has increased and the profitability ratio has decreased. Keywords: Ratio Analysis, Performance, Finance